2023
DOI: 10.3390/w15223882
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Meteorological Drought and Its Impact on Vegetation in an Arid and Semi-Arid Region

Weijie Zhang,
Zipeng Wang,
Hexin Lai
et al.

Abstract: Under the background of global climate warming, meteorological drought disasters have become increasingly frequent. Different vegetation types exhibit varying responses to drought, thus, exploring the heterogeneity of the impact of meteorological drought on vegetation is particularly important. In this study, we focused on Inner Mongolia (IM) as the research area and employed Standardized Precipitation Evapotranspiration Index (SPEI) and Vegetation Health Index (VHI) as meteorological drought and vegetation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…SPEI combines the precipitation and potential evapotranspiration data simultaneously to evaluate drought conditions, effectively capturing the balance between water supply (precipitation) and water demand (evapotranspiration) [12,14]. It has been concluded that SPEI is superior to SPI and PDSI because it calculates drought across various timescales, has a simple methodology, and provides robust results [15][16][17]. Moreover, SPEI is supposed to be a much more reasonable approach for analyzing the impacts of climate change on drought occurrence [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…SPEI combines the precipitation and potential evapotranspiration data simultaneously to evaluate drought conditions, effectively capturing the balance between water supply (precipitation) and water demand (evapotranspiration) [12,14]. It has been concluded that SPEI is superior to SPI and PDSI because it calculates drought across various timescales, has a simple methodology, and provides robust results [15][16][17]. Moreover, SPEI is supposed to be a much more reasonable approach for analyzing the impacts of climate change on drought occurrence [12,18].…”
Section: Introductionmentioning
confidence: 99%